Challenges and Opportunities of Decentralized Educational Planning in Nepal - Chaudhary, Sadhana (Chhahari छहारी, 2026)
The decentralization of educational planning and management has been one of the most significant governance reforms in Nepal following the adoption of the 2015 Constitution and the federal system of government. This research explores the challenges and opportunities that have emerged from the implementation of decentralized educational planning at the local level. It examines the degree to which local governments have been able to assume their constitutionally mandated responsibilities for education management, planning, and service delivery. Using a qualitative descriptive research design supported by document review and semi-structured interviews with education officials, headteachers, and municipal representatives, the study reveals that decentralization has created both opportunities for local empowerment and barriers related to capacity, coordination, and resource constraints.Major challenges include limited human and technical capacity in educational planning, overlapping responsibilities among government levels, inadequate fiscal autonomy, and political interference in decision-making. However, decentralization has also fostered significant opportunities: increased community participation, local-level innovation, and context-sensitive planning approaches. The findings suggest that Nepal’s education system stands at a crossroads either to consolidate decentralization as a transformative process or risk it becoming symbolic without meaningful empowerment. The study concludes by recommending structured capacity building, strengthened intergovernmental coordination, and policy clarity to enable local governments to exercise genuine autonomy in educational planning and management.